Determinants of Financial Literacy and its Effect on Financial Wellbeing-A Study on Young Population (Global Journal of Management and Business Research, 2022)
Over the past few years the world economy has been declining and the recession has caused inflation unemployment and a decline in financial well-being The decline in financial well-being has harmful effects on mental and physical health It creates problems of stress anxiety depression and suicide in our society Taft et al 2013 Financial literacy has become a much-discussed topic in recent years for the financial empowerment of people and their lives